Local Reconstruction in the Muon Detectors - Bruno, Giacomo; Cox, Peter Timothy; Lacaprara, Stefano; Neumeister, Norbert; Van de Vyver, Bart; Villa, Stefano; Wilkinson, Richard (2002)
We describe local reconstruction in the component subdetectors Resistive Plate Chambers, Cathode Strip Chambers, and Drift Tubes of the CMS muon subsystem. Local reconstruction' is here used to denote the sequence of steps leading from the raw data to the first-level reconstructed data which are the input to the muon track reconstruction. The algorithms described are those used in version 6.2.3 of ORCA, the CMS reconstruction software package. Particular emphasis is given to recent improvements, with a discussion of the current performance.